Sposoby zarządzania ryzykiem działalności gospodarczej w przedsiębiorstwach produkujących pasze - Florek, Joanna; Czerwińska-Kayzer, Dorota (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The main target of the article was to present and evaluate the financial situation as well as the identification of methods of adverse price change risk management used in the animal feed producing enterprises. The presented research has showed that animal feed producing enterprises characterized by good financial condition. The studies showed a low level of activity in risk management. The main threat of economic activity is the price risk.